Cytologic analysis of the mammary papillar discharge in a canine micropapillary carcinoma. (14th July 2015) - Cassali, Geovanni Dantas; Monteiro, Lidianne Narducci; Gamba, Conrado de Oliveira; Damasceno, Karine Araújo; de Campos, Cecília Bonolo; Salgado, Breno Souza
Abstract: This is a report on the cytologic analysis of the mammary papillar discharge in a 7‐year‐old female Doberman dog with an invasive micropapillary carcinoma. Cytologic evaluation of nipple discharge is a well‐known method for the rapid diagnosis of breast cancer in women. However, there is no previous report regarding the use of this technique for assessing mammary tumors in dogs. The aim of this study was to describe the use of mammary papillar discharge cytology for diagnosing a micropapillary carcinoma in a dog. Cytologically, evaluation of the papillar discharge revealed cells arranged in clusters in a papillary pattern or in a morula‐like arrangement, suggesting the diagnosis of a micropapillary carcinoma, which was subsequently confirmed by histopathology. Thus, mammary papillar discharge cytology should be considered as an ancillary method for evaluating mammary diseases in dogs.